SENSORY EVALUATION BROILER MEAT ON MAINTENANCE OF CLOSED HOUSE SYSTEMS WITH DIFFERENT AREA - R., Kurniawan; Miwada, I N. S.; Ariana, I N. T. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
Research on the sensory evaluation of broiler meat in the maintenance of closed house systems with different areas has been carried out to determine the quality of broiler meat sesnsoris raised in closed house systems with different areas, and determine the best area in the broiler maintenance closed house system against the sensory skin of broiler meat. This is done by the simple pattern Complete Random design (RAL) method, namely with 4 treatments, where Z1 Area 1 (0-30 m from the inlet) ; Z2 Area 2 ( 30-60 m from the inlet) ; Z3 Area 3 (60- 90 m from the inlet) ; Z4 Area 4 (90-120 m from the inlet), then 4 tests, namely in each treatment, sampling was carried out on 4 tititk randomly selected and then at each point broiler samples will be taken which will be used in the organoleptic test, in the organoleptic test carried out by inviting 25 panelists to assess the sensory quality of broiler meat. The results showed that the treatment of P1, P2, P3 and P4 did not differ markedly (P>0.05) with an average value of 3.88-4.00. the degree of liking for the taste of broiler meat P1, P2, P3 and P4 does not differ markedly (P>0.05) with an average nilia of 3.52-3.84. The panelists' liking for broiler meat color showed no noticeable difference (P>0.05) between P1, P2, P3 and P4 treatments with a treatment value of 3.76-3.92 (tending to like). the panelists' liking, towards the aroma of broiler meat showed that the treatment of P1, P2, P3 and P4 did not differ markedly (P>0.05) with an average value of 3.76 3.96 (tending to like). the degree of liking for the texture of broiler meat P1, P2, P3 and P4 does not differ markedly (P>0.05) with an average value of 3.76-4.00 (tends to like). Overall acceptance of broiler meat in the Closed House system with different regions showed that the P1, P2, P3 and P4 treatments were not significantly different (P>0.05) with an average value of 3.88 4.00 (tend to be neutral). The conclusion of this study is that the differences in broiler rearing zones with the closed house system do not have a different effect on the sensory quality of broiler meat. Sensory indicators such as taste, aroma, color, texture and overall acceptability in assessing meat quality are the same.